2004
DOI: 10.1056/nejmoa032441
|View full text |Cite
|
Sign up to set email alerts
|

A Polymer-Based, Paclitaxel-Eluting Stent in Patients with Coronary Artery Disease

Abstract: As compared with bare-metal stents, the slow-release, polymer-based, paclitaxel-eluting stent is safe and markedly reduces the rates of clinical and angiographic restenosis at nine months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
776
6
50

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 2,522 publications
(857 citation statements)
references
References 29 publications
16
776
6
50
Order By: Relevance
“…35 In contemporary emergency, urgent, or elective stent and drug-eluting stent (DES) clinical trials and registries, adjustments for these factors largely eradicate any sex differences, dispelling the notion of a sex-specific mortality risk. 28,32,36,37 In the majority of studies, adjusted longterm mortality rates after PCI (1 year and beyond) are similar for men and women (Figures 1 and 2). 23,28,38 -40 Historically, restenosis and revascularization rates have not been well defined for women, partly because of the small sample of women in prospective trials with systematic angiographic follow-up, as well as the paucity of published sex-subset analyses.…”
Section: Sex Differences In Outcomes Of Pcimentioning
confidence: 92%
“…35 In contemporary emergency, urgent, or elective stent and drug-eluting stent (DES) clinical trials and registries, adjustments for these factors largely eradicate any sex differences, dispelling the notion of a sex-specific mortality risk. 28,32,36,37 In the majority of studies, adjusted longterm mortality rates after PCI (1 year and beyond) are similar for men and women (Figures 1 and 2). 23,28,38 -40 Historically, restenosis and revascularization rates have not been well defined for women, partly because of the small sample of women in prospective trials with systematic angiographic follow-up, as well as the paucity of published sex-subset analyses.…”
Section: Sex Differences In Outcomes Of Pcimentioning
confidence: 92%
“…Drug‐eluting stents (DESs) have reduced restenosis by inhibiting neointimal growth,1, 2 but there are still certain indications of late stent failure such as late stent thrombosis and restenosis. Although incomplete endothelialization was reported as the primary substrate of late stent thrombosis in an initial pathological study,3, 4 recent reports revealed that abnormal vascular responses are also responsible for the occurrence of late stent failure 5, 6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…Although the advantage of drug-eluting stents (DESs) versus bare metal stents (BMSs) has been well documented for native coronary artery disease, [1][2][3] data are limited for the systematic evaluation of DESs and BMSs in saphenous vein graft (SVG) disease. The clinical studies undertaken to evaluate DESs in SVG were underpowered, and the results of these studies were inconsistent with respect to the rates of major adverse cardiac events, death, myocardial infarction (MI), and target vessel revascularization (TVR).…”
mentioning
confidence: 99%